Влияние избытка аммиака на выделение меди и никеля на вращающемся дисковом электроде - Майзелис, Антонина Александровна; Байрачный, Борис Иванович; Трубникова, Лариса Валентиновна (НТУ "ХПИ", 2011)
The influence of free ammonia excess in the electrolyte on the copper, nickel and copper-nickel alloys electrodeposition on the rotating disk electrode in a weak alkaline electrolyte is presented. The increase in the ammonia excess in the electrolyte suppresses the stepped discharge of copper ions, reduces the limiting current of the copper and nickel electrodeposition, and reduces the influence of the stirring intensity at the region of the hydrogen evolution.
Keywords: электролит; среда слабощелочная; ионы; водород